2008
DOI: 10.1007/bf03168237
|View full text |Cite
|
Sign up to set email alerts
|

Cambios en el ECG y la actividad enzimática en corazón de rata tras infarto de miocardio: efecto de la TPP y del MnCl2

Abstract: Heart infarction is one of the main causes of death in the human population. Assurance of a sufficient level of bioenergetic processes is very important for the heart after infarction. Mn2+ as well as thiamine pyrophosphate (TPP) are positive effectors of the pyruvate dehydrogenase complex (PDH) and the 2-oxoglutarate dehydrogenase complex (OGDH), both of which play a very important role in the Krebs cycle. Thus, we have established the effect of MnCl2 (10mg/kg) and TPP (20mg/kg)--4 injections every 12 h--on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Precipitated cellular debris was centrifuged for 15 min at 12 000 g at 4°C, and the clarified supernatants were used for activity measurements. The activity of all TDP-dependent enzymes was determined spectrophotometrically, on the basis of NADH detection at k = 340 nm (Kimmerer, 1987;Gibson et al, 1988;Chamberlain et al, 1996;Tylicki et al, 2008).…”
Section: Extract Preparation and Enzyme Activity Assaysmentioning
confidence: 99%
“…Precipitated cellular debris was centrifuged for 15 min at 12 000 g at 4°C, and the clarified supernatants were used for activity measurements. The activity of all TDP-dependent enzymes was determined spectrophotometrically, on the basis of NADH detection at k = 340 nm (Kimmerer, 1987;Gibson et al, 1988;Chamberlain et al, 1996;Tylicki et al, 2008).…”
Section: Extract Preparation and Enzyme Activity Assaysmentioning
confidence: 99%
“…Notably, previous studies revealed the significant loss of LIFR in failing heart both in humans [ 29 ] and rats [ 30 ]. Also, decreased OGDH activity in rat hearts after myocardial infarction has been observed [ 31 ]. Moreover, hsa-miR-339-5p has been reported to be up-regulated after human left ventricular ischemia [ 32 ] and hsa-miR-134 was an essential regulator in cardiogenesis whose increased expression was strongly associated with increased risk of mortality or heart failure [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ECG waveforms of MI group were completely different compared to the normal ECG. The ST segment of ECG, shown in Figure 14, was noticeably elevated, suggesting that MI was successfully induced [36][37][38] and MI can be diagnosed with our device. differed slightly depending on the rats and the position of the devices, the normal rats showed normal characteristic features of rat ECG using our device [34,35].…”
Section: In Vivo Experimentsmentioning
confidence: 87%
“…The ECG waveforms of MI group were completely different compared to the normal ECG. The ST segment of ECG, shown in Figure 14, was noticeably elevated, suggesting that MI was successfully induced [36][37][38] and MI can be diagnosed with our device. Isoproterenol (30 ug/kg, 300 ul) and Diltiazem (10 mg/kg, 300 ul) were used to make change in HR.…”
Section: In Vivo Experimentsmentioning
confidence: 87%